Transcriptional and environmental control of bacterial denitrification and N2O emissions. Issue 5 (20th December 2017) - Gaimster, Hannah; Alston, Mark; Richardson, David J; Gates, Andrew J; Rowley, Gary
Abstract: In oxygen-limited environments, denitrifying bacteria can switch from oxygen-dependent respiration to nitrate (NO3 − ) respiration in which the NO3 − is sequentially reduced via nitrite (NO2 − ), nitric oxide (NO) and nitrous oxide (N2 O) to dinitrogen (N2 ). However, atmospheric N2 O continues to rise, a significant proportion of which is microbial in origin. This implies that the enzyme responsible for N2 O reduction, nitrous oxide reductase (NosZ), does not always carry out the final step of denitrification either efficiently or in synchrony with the rest of the pathway. Despite a solid understanding of the biochemistry underpinning denitrification, there is a relatively poor understanding of how environmental signals and respective transcriptional regulators control expression of the denitrification apparatus. This minireview describes the current picture for transcriptional regulation of denitrification in the model bacterium, Paracoccus denitrificans, highlighting differences in other denitrifying bacteria where appropriate, as well as gaps in our understanding. Alongside this, the emerging role of small regulatory RNAs in regulation of denitrification is discussed. We conclude by speculating how this information, aside from providing a better understanding of the denitrification process, can be translated into development of novel greenhouse gas mitigation strategies. Abstract : Denitrification is an important biogeochemical process, which when disrupted, leads to production of a greenhouse gas, nitrous oxide. Here we describe the factors which are important in regulating this process.